(3JgPjH GdceGd aiCSeGA GdQLGds - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s; (3YHO GdZfj Hf YHO GdhGMO Hf Ydj Hf SQhQ GdebOSj GdLeGYjdj GdOeTbj GdMfHdj, CHh eMeO, Jbj GdOjf,J (B600 (3g` s
(3ChdgG (B:s
(3JHOC ef Yhf Hf YeGQI s
(3BNQgG (B:s
(3bJjHI Hf SYjO s
(3fSNI SGOSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B275s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B45 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI HOeTb (B((3MOjK (B365) s
Keywords: (3GdJGQjNs